POLA PENYELESAIAN PERSELISIHAN HUBUNGAN INDUSTRIAL SECARA WAJIB SEBAGAI PILIHAN PARA PIHAK DALAM MENYELESAIKAN PERSELISIHANNYA - Rahmawati Kusuma; Zaeni Asyhadie; Lalu Hadi Adha (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Efforts to provide legal protection for workers/labourers in an employment relationship are a follow-up to the enforcement of human rights. The acknowledgment of equality before the law between employers and workers/labourers is a juridical consequence of the meaning contained in Article 27 of the 1945 Constitution, so Iman Soepomo (1985: 7) wrote,